School finance - Thro, William E. (Debating issues in American education ;, 2012)
Provides views on multiple sides of curriculum and instruction issues in America's schools and offers more in-depth resources for further exploration. This volume examines school finance, covering such varied issues as additional fees, charger schools, equity vs. adequacy, federal mandates and funding, merit pay for teachers, property taxes and local revenues.